2013
DOI: 10.1097/hjh.0b013e3283638b1a
|View full text |Cite
|
Sign up to set email alerts
|

Low dose spironolactone reduces blood pressure in patients with resistant hypertension and type 2 diabetes mellitus

Abstract: Low dose spironolactone exerts significant BP and urinary albumin creatinine ratio lowering effects in high-risk patients with resistant hypertension and type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 43 publications
2
66
1
2
Order By: Relevance
“…In line with the data published by Hanselin et al, 23 the association of 2 or even 3 renin-angiotensin system blockers, a less efficacious and potentially harmful drug combination, 24,25 was used in 22% of patients, whereas diuretics (82%) and, notably, calcium antagonists (73%) were still underused. In particular, low-dose spironolactone, a recommended drug in patients with resistant hypertension 26,27 was prescribed in only 26% of patients (Table 2), even in a subset with normal renal function, which is much higher than in the US database explored by Hanselin et al 23 (5.9%) and slightly better than in 2 other cohorts of patients referred in The Utrecht center did not have detailed information on file on the subclassification of renin system inhibitors or diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the data published by Hanselin et al, 23 the association of 2 or even 3 renin-angiotensin system blockers, a less efficacious and potentially harmful drug combination, 24,25 was used in 22% of patients, whereas diuretics (82%) and, notably, calcium antagonists (73%) were still underused. In particular, low-dose spironolactone, a recommended drug in patients with resistant hypertension 26,27 was prescribed in only 26% of patients (Table 2), even in a subset with normal renal function, which is much higher than in the US database explored by Hanselin et al 23 (5.9%) and slightly better than in 2 other cohorts of patients referred in The Utrecht center did not have detailed information on file on the subclassification of renin system inhibitors or diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous trials have shown that unlike office BP, the 24-hour ambulatory BP is less or no subject to the white-coat effect. [52][53][54][55][56] Therefore, the placebo or white-coat effect seem not to contribute to the wide scatter in Symplicity HTN-3, 51 which was not different to the previous uncontrolled trials. 26,[40][41][42] For patients in Symplicity HTN-3, changes in medication were permissible until 2 weeks before the procedure.…”
Section: Open Questions Lack Of Blinded Randomized Datamentioning
confidence: 99%
“…This is obviously not the case because it just represents energy delivery to the arterial wall, and endothelial edema, not nerve ablation. Noteworthy, in 68% of patients 0 or 1 notch was observed (54), suggesting that energy delivery was substandard. Finally, there are interesting findings in the subgroup composition.…”
Section: Open Questions Lack Of Blinded Randomized Datamentioning
confidence: 99%
“…In another multicenter, double-blind, placebo-controlled study in patients with 24-hour BP >130/80 mm Hg, despite triple antihypertensive therapy and type 2 diabetes mellitus, the effect of adding 25 mg of spironolactone (n=57) or placebo (n=55) has been evaluated. 8 Placebo-corrected BP changes were −8.9 mm Hg and −3.7 mm Hg for 24-hour SBP and diastolic BP (P<0.001), respectively. The reductions of BP in the above-mentioned trials, including PRAGUE-15, were significantly lower compared with BP reductions documented in previous trials.…”
Section: Aldosterone Antagonists In Resistantmentioning
confidence: 99%